PENGARUH PEMBERIAN KOMPENSASI DAN PENGALAMAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN PT. DIPO INTERNASIONAL PAHALA OTOMOTIF BANDA ACEH - Ayi Satria Yudha; Nasri Zarman; Banta Karollah (SI-MEN, 2021)
Compensation and work experience are things that need to be done to increase employee morale in achieving organizational goals. This study aims to determine the effect of compensation and work experience on employee morale at PT. Dipo International Pahala Otomotif Banda Aceh. This research uses quantitative methods . The sample size in this study amounted to 47 people with a total sampling technique of sampling. Data collection techniques were carried out by observation and interviews. Data analysis was performed using linear regression. The results showed that the provision of compensation and work experience had a significant effect on work morale were 0.448. The results of the regression coefficient of 0.478 for compensation and work experience of 0.283. Meanwhile, for hypothesis testing (t count > t table), the results of the t test in this study were compensation (6.855 > 2.015) with a significance of 0.000 and work experience (9.151 > 2.015) with a significance of 0.003. Keywords: Compensation, Experience and Work Spirit